The Role of Economic Uncertainty in Rising Populism in the EU - Giray Gozgor (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This paper examines the impact of economic uncertainty shocks on the populist voting behavior in the panel dataset of 24 European Union (EU) countries for the period from 1980 to 2020. In so doing, we focus on the shares of total populism, right-wing populism, and left-wing populism votes as well as a new indicator of economic uncertainty, so-called, the “World Uncertainty Index (WUI).” Using the fixed-effects, bias-corrected least-squares dummy variable (LSDVC), and Instrumental Variables (IV) estimations, we show that a higher level of the WUI is positively related to total populism and right-wing populist voting behavior. The baseline results remain consistent when we deal with potential issues of endogeneity, to address omitted variable bias, and to exclude the outliers.
Keywords: D72; D81; C33; 330; populist attitudes in the European Union; voting behaviour; right-wing populism; left-wing populism; uncertainty shocks; economic policy uncertainty